1966
DOI: 10.1002/pol.1966.150040610
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of aromatic nuclei. X. Polymerization of benzene to p‐polyphenyl oligomers by nitrogen dioxide—aluminum chloride

Abstract: SynopsisBenzene was polymerized to p-polyphenyl oligomers by nitrogen dioxidealuminum chloride. Polymer production was favored by AlClS:N02 ratios of at least 2, long reaction times, and higher temperatures. Evidence for the polymer structure was obtained from elemental analyses, oxidative degradation, solubility, molecular weight, functional group tests, low molecular weight products, and infrared and ultraviolet spectra. The chains contained small amounts of chloro, amino, hydroxyl, and carboxyl substituents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1967
1967
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…This process is commonly known as the Scholl reaction (Figure , black scheme) and is still used for various aryl–aryl couplings . It was found that the resulting molecular weight was heavily dependent on the reaction temperature and concentrations, while the lack of solubility of the PPP made it impossible to fully characterize and process polymers of significant size (molecular weight greater than 2–3 kg/mol). …”
Section: Introduction To Polyphenylenementioning
confidence: 99%
“…This process is commonly known as the Scholl reaction (Figure , black scheme) and is still used for various aryl–aryl couplings . It was found that the resulting molecular weight was heavily dependent on the reaction temperature and concentrations, while the lack of solubility of the PPP made it impossible to fully characterize and process polymers of significant size (molecular weight greater than 2–3 kg/mol). …”
Section: Introduction To Polyphenylenementioning
confidence: 99%